Pendekatan Guru PAI dalam Menerapkan Nilai-Nilai Religiusitas di SMP Negeri 1 Sultan Daulat Kota Subulussalam - M. Yasin M. Yasin; Saifullah Idris; Masbur Masbur (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
The problems in this study are translated into 3 problem formulations as follows: (1) What is the approach taken by PAI teachers in implementing Religiosity Values ​​at Sultan Daulat 1 Public Middle School? (2) What are the obstacles and challenges faced by PAI teachers in implementing religious values ​​at SMP Negeri 1 Sultan Daulat, Subulussalam City? This study used a qualitative descriptive research method with data collection techniques through interviews, observation, and documents. Data analysis techniques use data reduction, data display, and conclusions or verification. The findings of this study are as follows: The efforts of Islamic Religious Education Teachers in instilling the values ​​of worship through religious activities in students of SMP Negeri 1 Sultan Daulat include holding dhuhur prayers in congregation, holding dhuha prayers for classes that have PAI subjects at first and commemorating religious holidays such as the commemoration of Isra' Mi'raj, Mawlid Nabi, Istighasah, holding call to prayer competitions, BTQ, qira'at, speeches, shalawatan, compensation for orphans, Ramadhan huts, breaking the fast together, tarawih prayers in congregation, management of zakat fitrah, and the slaughter of sacrificial animals. The efforts of Islamic Religious Education Teachers in instilling moral values ​​through religious activities in students of Sultan Daulat 1 Public Middle School include getting used to applying the school's Islamic culture in the form of 4S (smile, greet, greet, be polite) and 2M (turn off and guide) motorized vehicles in the school area and put up slogans that contain religious elements.